2015
DOI: 10.1016/j.abb.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Actions of β-apo-carotenoids in differentiating cells: Differential effects in P19 cells and 3T3-L1 adipocytes

Abstract: β-Apo-carotenoids, including β-apo-13-carotenone and β-apo-14′-carotenal, are potent retinoic acid receptor (RAR) antagonists in transactivation assays. We asked how these influence RAR-dependent processes in living cells. Initially, we explored the effects of β-apo-13-carotenone and β-apo-14′-carotenal on P19 cells, a mouse embryonal carcinoma cell line that differentiates into neurons when treated with all-trans-retinoic acid. Treatment of P19 cells with either compound failed to block all-trans-retinoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Also, ␤-apo-14Ј-carotenal effectively inhibited agonist-induced RXR␣, PPAR␣, and PPAR␥ activation, decreasing adipogenesis (16). These cell culture-based experiments demonstrated that specific ␤-apocarotenoids function as nuclear receptor antagonists exerting an anti-vitamin A (retinoic acid) activity (17). Not only apo10AL (42) but also apo10OL (9) was detected in tissues of mice fed BC-containing diets even though the enzymes that could catalyze the conversion of ␤-apocarotenal, the primary asymmetric cleavage product of BC, into ␤-apocarotenol have not been identified.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Also, ␤-apo-14Ј-carotenal effectively inhibited agonist-induced RXR␣, PPAR␣, and PPAR␥ activation, decreasing adipogenesis (16). These cell culture-based experiments demonstrated that specific ␤-apocarotenoids function as nuclear receptor antagonists exerting an anti-vitamin A (retinoic acid) activity (17). Not only apo10AL (42) but also apo10OL (9) was detected in tissues of mice fed BC-containing diets even though the enzymes that could catalyze the conversion of ␤-apocarotenal, the primary asymmetric cleavage product of BC, into ␤-apocarotenol have not been identified.…”
Section: Discussionmentioning
confidence: 85%
“…This cleavage product can ultimately yield one molecule of retinoic acid; how- ever, it can also function itself as a transcriptional regulator by antagonizing retinoic acid actions (13)(14)(15)(16)(17). We previously showed that 24 h after a single maternal administration of BC at midgestation, Bco2 mRNA levels increased, whereas Bco1 transcription was down-regulated in the placentas of WT dams (25).…”
Section: Bc-dependent Transcriptional Up-regulation Of Placental Mttp Ismentioning
confidence: 99%
See 1 more Smart Citation
“…β-Apo-10'-carotenoic acid increased expression of LPL and AP2, but did not have a significant influence on expression levels of adiponectin or PPARγ. 88 β-Apo-14'-carotenal, β-apo-14'-carotenoic acid, and β-apo-13-carotenone were demonstrated to be RAR antagonists in transactivation assays. 89 However, β-apo-13-carotenone and β-apo-10'-carotenoic acid lack RAR-antagonist activity.…”
Section: Pparγ Activation In Carotenoidinhibited Cancer-cell Prolifermentioning
confidence: 99%
“…They failed to diminish the inhibitory effects of a relatively large dose of exogenous all-trans-RA on adipocyte differentiation. 88 It is evident that β-carotene has a complex influence on PPARγ-regulated pathways controlling adipogenesis. An adipose tissue-specific conversion of β-carotene via carotenoid oxygenases can influence the activities of key transcription factors.…”
Section: Pparγ Activation In Carotenoidinhibited Cancer-cell Prolifermentioning
confidence: 99%